Determinants of Outputs and Productivity of Small-Scale Okra Farmers in Gwagwalada Area Council, Federal Capital Territory (FCT), Nigeria - Olohungbebe, Sheu Ahmad; Olawoye, Tosin (FUDMA Journal of Sciences, 2026)
This study examines the output determinants and productivity of small-scale okra production among rural farmers in Gwagwalada Area Council, Federal Capital Territory, Nigeria. A multistage sampling technique was employed to select 77 okra farmers from major producing communities, and primary data were collected using a structured questionnaire. Data were analyzed using descriptive statistics, Ordinary least squares (OLS) regression, Total factor productivity (TFP) ratio analysis, Multiple regression on log-transformed data, and the Garrett ranking technique. Findings revealed that farm size (p < 0.01) and access to extension services (p < 0.10) were the significant positive determinants of okra output. The mean TFP of 0.732 indicated that the majority of farmers (79.2%) could not fully recover production costs from output value, reflecting widespread inefficiency. Farming experience significantly and positively influenced TFP (p < 0.01), while older farmers’ age exerted a negative effect (p < 0.10). The major constraints faced by the respondents were, pest and disease infestation, price volatility, and high input costs. This study therefore recommends targeted policy interventions such as subsidized integrated pest management programs and affordable input delivery systems to close the productivity gap among smallholder okra producers in the FCT.
Keywords: Okra production; Small scale farmers; Total factor productivity; Output determinants; Federal Capital Territory